Studi Diagenesis Batugamping Formasi Meluhu Daerah Toronipa, Kecamatan Soropia, Kabupaten Konawe, Provinsi Sulawesi Tenggara - Hasria Hasria; Abdul Jalil; Masri Masri; Ali Okto; Bahdad Bahdad; Sara Septiana (Jurusan Teknik Pertambangan, Fakultas Sains dan Teknik, Universitas Bangka Belitung, 2023)
The research area is administratively located at Toronipa, Soropia District, Konawe Regency, Southeast Sulawesi Province. The purpose of this study was to determine the type of limestone, the diagenes process and the environment of limestone diagenesis in the Meluhu Formation. The method used in this research is the petrographic method. The results showed that the types of limestone in the study area were wackestone and packstone which had undergone a diagenesis process in the form of cementation, microbial micritization, neomorphism, and dissolution. The limestone diagenesis environment in the Meluhu Formation originates from the marine phreatic, meteoric phereatic, and meteoric vadose diagenesis environments.